ANALISIS GRAMSCI TERHADAP IDE PEMERINTAH MEKSIKO PADA GERAKAN ZAPATISTA (PERIODE 1994-2006) - Giri Wijayanti, Kartika (Transformasi, 2014)
This research discusses Antonio Gramsci's analysis of the idea of the Mexican Government forthe period 1994-2006 that included three presidents, Carlos Salinas, Ernesto Zedillo and VicenteFox Quesada on the Zapatista movement. Zapatistas fought after the effectiveness of NAFTA onJanuary 1, 1994, which makes society increasingly impoverished Chiapas. In response to theZapatista movement, the Mexican government acts motivated by different ideas.The authors take the theory approach with the theory of Antonio Gramsci on hegemony andcounter hegemony to analyze the idea that owned by each president.Key Words : Gramsci, Hegemony, Counter Hegemony.